THE INTERACTION BETWEEN DIGITAL DIPLOMACY AND PUBLIC DIPLOMACY OF THE UNITED STATES - Izzatullayev Bobirjon; Azimov Khakimali Imamovich (Modern American Journals, 2026)
This article examines the interaction between U.S. digital diplomacy and public diplomacy, highlighting their parallel evolution in the context of ICT expansion and Web 2.0 technologies. It analyzes how online platforms enhance soft power, public engagement, and policy advocacy, while also generating challenges such as disinformation and domestic backlash. The study argues that effective foreign policy communication increasingly depends on integrating both diplomatic approaches in an evolving global information environment.
Keywords: Digital diplomacy; Public diplomacy; United States foreign policy; ICT; Web 2.0; Soft power; Policy advocacy; Online communication; International relations; Information diplomacy.